Convergence and the right to communicate : assessing the application of media law to the internet - Mac Síthigh, Daithí (Trinity College (Dublin, Ireland). School of Law, 2010)
The regulation of radio and television broadcasting through law is an established area of interest. The idea of 'cyberlaw' or Internet law has, after a period of initial division and reflection, emerged as an important area of research in law. This thesis draws upon both traditions of legal scholarship, as well as certain concepts from media and communications studies, to assess the role of media law and of other forms of control in what is a changing cultural and technological environment. Although attempts to develop a new agenda for global communications through UNESCO were not entirely successful, the idea of the 'right to communicate' as a fundamental right has much to offer. The work of Harold Innis and Lawrence Lessig is assessed, with it being argued that both approaches have something to add to an analysis of where ‘law’ for the converging media is to be found.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin